(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract:This research aims to explain about the role of technical implementing unit of Manado city or samsat Manado in preventing and overcoming counterfeiting of motor vehicle letters. This research uses descriptive method of qualitative approach, and data collection technique done by observation, interview technique, and documentation. The number of informants as many as 10 people. In this research using the measurement of duties and functions of the samsat office in terms of where the approach of this process include (i) planning, (ii) coordination, (iii) coaching, (iv) control of service tasks. The result of the research shows that the role of samsat manado in prevention against counterfeiting of motor vehicle letters is : a. Conducting motor vehicle document research by conducting cross check against frame number and engine number to motor vehicle; b. Receive and examine the results of physical inspection of motor vehicles to be adjusted to the documents of motor vehicles; c. The selection of good safety signs in the motor vehicle letters, so that the letter of the motor vehicle is difficult to forge. Countermeasures of criminal counterfeiting of letters conducted by samsat Manado party by blocking motor vehicle letters. The role of samsat in this case only as an informant only. Samsat has no authority in investigating cases of counterfeiting of motor vehicles letters. Samsat still cooperate with the police if the police still need the help of samsat for completeness of ranmor files or as expert witnesses. Keywords : Role, SAMSAT, Counterfeiting